THE ROLE OF INFORMATION TECHNOLOGY MEDIA, COMMUNICATION AND IT-BASED LEARNING PROCESSES DURING THE COVID-19 PANDEMIC - Ina Monica Lamintang (Entrepreneurship Undergraduate Program at Amkop Business School, 2023)
The provision of media in a school is very influential on the learning achievement of students, because the media is very helpful in the learning process. Media that is currently starting to be promoted in every school is IT-based media, such as the internet, the use of LCD during the learning process, the use of e-books, computers / laptops and others. The need for media in the learning process is certainly not only for schools in urban areas where access is easier, but schools in remote areas are also necessary even though access is more difficult. This is an anticipation of the inequality of education in remote areas with education in big cities. The procurement of IT-based learning media, which in this case greatly affects the learning achievement of students needs to be held in every school, not only in city schools but even remote schools as an effort to eliminate public perceptions between students who go to school in the city and students who go to school in the village. In addition, the existence of IT-based learning in all schools, will minimize the inequality of education in remote areas and in cities.